Evaluation Studies on Education in Occupational Safety and Health: Inspiration for Developing Economies - Frank J. van Dijk; Marija Bubas; Paul B. Smits (Ubiquity Press, 2015)
Background: Education and training of students, workers, and professionals are essential for occupational safety and health (OSH). We noticed a lack of debate on how to advance coverage and quality of OSH education given high shortages in developing economies. Objectives: International discussion on future options might be stimulated by an overview of recent studies. Methods: We employed a search of the Cochrane Library and PubMed/MEDLINE databases for articles from the last decade on evaluation of OSH education. Findings: We selected 121 relevant studies and 6 Cochrane reviews. Most studies came from the United States, Western Europe, and Asia. Studies from low-income countries were scarce. From a global perspective, the number of evaluation studies found was disappointingly low and the quality needs improvement. Most commonly workers' education was evaluated, less often education of students, supervisors, and OSH professionals. Interactive e-cases and e-learning modules, video conferences, and distance discussion boards are inspiring educational methods, but also participatory workshops and educational plays. Ways to find access to underserved populations were presented and evaluated, such as educational campaigns, farm safety days, and OSH expert-supported initiatives of industrial branch organizations, schools, and primary, community, or hospital-based health care. Newly educated groups were immigrant workers training colleagues, workers with a disease, managers, and family physicians. Conclusions: Developing economies can take advantage of a variety of online facilities improving coverage and quality of education. Blended education including face-to-face contacts and a participatory approach might be preferred. For workers, minor isolated educational efforts are less effective than enhanced education or education as part of multifaceted preventive programs. Collaboration of OSH experts with other organizations offers opportunities to reach underserved worker populations. Increasing international collaboration is a promise for the future. National legislation and government support is necessary, placing OSH education high on the national agenda, with special attention for most needed professionals and for underserved workers in high-risk jobs such as in the informal sector. International support can be boosted by a high-level international task force on education and training, funded programming, and a global online platform.